(untitled) (International journal of artificial intelligence, 2025)
This article examines the significance of regional organizational mechanisms in enhancing gross regional product (GRP) within Uzbekistan’s regional economies. It explores how structured coordination, effective resource allocation, and strategic governance frameworks drive economic growth. Official data indicate that regions with robust organizational mechanisms achieved a 10% higher GRP growth compared to less coordinated regions from 2020 to 2023. Grounded in regional development theory and supported by case studies, the study addresses challenges such as bureaucratic inefficiencies and resource disparities. Recommendations include strengthening inter-agency collaboration and adopting digital governance tools to optimize regional economic performance.